Survival of dogs with myxomatous mitral valve disease administered preclinical pimobendan in comparison to pimobendan-naïve dogs from the onset of congestive heart failure - G. McAulay; M. Hills; J. Dukes-McEwan; E. Dutton; A. Jakubczak; D. Singleton; E. Bode; W. Yangwanitset; M. Hezzell (Journal of Veterinary Cardiology, 2026)

Symmetric Dimethylarginine for Risk Stratification of Cardioembolic Stroke - Johanna Ernst; Ilai Mick Albert Darius Kaulbarsch; Svenja L. Jochmann; Maria M. Gabriel; Ramona Schuppner; Ralf Lichtinghagen; Jens Martens-Lobenhoffer; Hannelore Ehrenreich; Stefanie M. Bode-Böger; Anika Grosshennig; Karin Weissenborn; Rieke Ringlstetter; et al. (Translational Stroke Research, 2026)
A significant proportion of ischemic strokes are classified as embolic stroke of undetermined source (ESUS), complicating secondary prevention. Nitric oxide metabolism is regulated by L-arginine (Arg), asymmetric (ADMA) and symmetric dimethylarginine (SDMA), contributing to increased cardiovascular risk. Previous studies suggest that SDMA and the ratio of Arg/SDMA help to detect atrial fibrillation (AF). We hypothesized that SDMA and Arg/SDMA improve diagnosis of cardioembolic stroke (CES), which may enable more accurate secondary prevention. This prospective nested case-control study included ischemic stroke patients (CES or ESUS) at Hannover Medical School between January 2022 and July 2023. Blood samples were collected after 24 h of stroke onset. ADMA, SDMA and Arg concentrations were measured and relevant biomarker ratios were calculated. Logistic regression and receiver operating curve analyses examined discriminatory biomarker performances for CES versus ESUS, alongside established clinical risk scores. 235 patients (107 CES, 128 ESUS) were analyzed. Arg/SDMA ratio and SDMA values showed comparable or better discriminatory power between CES and ESUS than clinical AF scores (AUC SDMA = 0.71 (95%CI: 0.64–0.77, p < 0.001); AUC Arg/SDMA = 0.74 (95%CI: 0.67–0.80, p < 0.001)). The same was true for AF detected after stroke (AFDAS) vs. ESUS. When combining Arg/SDMA-ratio and AS5F, the diagnostic accuracy was modestly improved compared to AS5F alone (DeltaAUC = 0.03 (95%CI: -0.06-0.11)). In conclusion, SDMA and Arg/SDMA ratio can serve as biomarkers for AF and AFDAS. While the additional predictive value in combination with clinical scores may be limited, these findings support the pathogenic role of the Arg/SDMA pathway in stroke pathophysiology. Trial Registration : The study is retrospectively registered in the German Clinical Trial Register (StudyID DRKS00038459).

Digitalization of the Retail Food Environment: Modernizing Food Access, Highlighting Health Equity, and Identifying Opportunities for Future Research and Practice - Jared T. McGuirt; Megan R. Winkler; Yarisbel Melo Herrera; Bree Bode; Caitlin M. Lowery; Maya Vadiveloo (Journal of Nutrition Education and Behavior, 2026)

Enhancing Nutrition Intervention Monitoring Through Computed Tomography Body Composition Assessment: A Case Study in Esophageal and Gastric Adenocarcinoma - M. Garcia Luis; C. Bury; A. Bode (Journal of the Academy of Nutrition and Dietetics, 2025)

P27-25 New approach for analysis of lung clearance kinetics in rats leading to a reduction of animal testing and improvement of chemical safety assessment - G. Bruer; M. Bode; K. Blümlein; O. Creutzenberg; D. Gõdecke; M. Breva; A. Garabatos; A. Burzlaff (Toxicology Letters, 2025)

Community Engaged Research Strategies Used in Food Retail Interventions: A Scoping Review - Ravneet Kaur; Kathryn M. Janda-Thomte; Bree Bode; Hadis Dastgerdized; Catherine Kaliszewski; Holly Hudson; Manorama Khare; Megan R. Winkler (Journal of the Academy of Nutrition and Dietetics, 2025)

Idiopathic spontaneous intracardiac microbubbles in an adult dog - L. Beeby; M. Martinez; E.F. Bode (Journal of Veterinary Cardiology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Incorporating Trauma-Informed Practices in Nutrition Education - Marissa McElrone; Palak Gupta; M. Elizabeth (Beth) Miller; Bree Bode; Kelseanna Hollis-Hansen (Journal of Nutrition Education and Behavior, 2025)

Clinical presentation, management, and survival in dogs with persistent atrial standstill in the United Kingdom - I. Sanz-Gonzalez; J. Aitken; B. Pedro; M. Martin; Y. Martinez Pereira; J. Dukes-McEwan; E.F. Bode; G.J. Culshaw (Journal of Veterinary Cardiology, 2024)

Human milk: From complex tailored nutrition to bioactive impact on child cognition and behavior - Carolina de Weerth; Anna-Katariina Aatsinki; Meghan B. Azad; Frank F. Bartol; Lars Bode; Maria Carmen Collado; Amanda M. Dettmer; Catherine J. Field; Meagan Guilfoyle; Katie Hinde; Aniko Korosi; Hellen Lustermans; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Macronutrients and Metabolizable Energy: Preliminary Findings from a Global Study to Characterize Nutrients in Donor Human Milk - M. Perrin; K. Mansen; K. Israel-Ballard; L. Bode (Journal of the Academy of Nutrition and Dietetics, 2023)

Differences in Left Ventricular Enlargement Secondary to Chronic Volume Loading Between English Springer Spaniels and Two Similar Sporting Breeds - D. Dickson; E. Bode; C. Linney; E. Dutton; D. Caivano; T. Bispo; J. Harris; M. Rishniw (Journal of Veterinary Cardiology, 2023)

Designing an expert-led Bayesian network to understand interactions between policy instruments for adoption of eco-friendly farming practices - Helen J. Mayfield; Rachel Eberhard; Christopher Baker; Umberto Baresi; Michael Bode; Anthea Coggan; Angela J. Dean; Felicity Deane; Evan Hamman; Diane Jarvis; Barton Loechel; Bruce M. Taylor; et al. (Environmental Science & Policy, 2023)

Zooplankton‐derived dissolved organic matter composition and its bioavailability to natural prokaryotic communities - Daniele De Corte; Marta M. Varela; Angeles M. Louro; Sarah K. Bercovici; Joaquín Valencia‐Vila; Eva Sintes; Federico Baltar; Tamara Rodríguez‐Ramos; Meinhard Simon; Antonio Bode; Thorsten Dittmar; Jutta Niggemann (Limnology and Oceanography, 2023)
Zooplankton grazing onphytoplankton promotes the release of particulate and dissolved organic matter (DOM) into the water column and therefore plays a key role in organic matter cycling in aquatic systems. Prokaryotes are the main DOM consumers in the ocean by actively remineralizing and transforming it, contributing to its molecular diversification. To explore the molecular composition of zooplankton‐derived DOM and its bioavailability to natural prokaryotic communities, the DOM generated by a mixed zooplankton community in the coastal Atlantic off Spain was used as substrate for a natural prokaryotic community and monitored over a ~ 5‐d incubation experiment. The molecular composition of solid‐phase extracted DOM was characterized via Fourier‐transform ion cyclotron resonance mass spectrometry. After ~ 4 d in the zooplankton‐derived DOM amended incubation, the prokaryotic community demonstrated a 17‐fold exponential increase in cell number. The prokaryotic growth resulted in a reduction in bulk dissolved organic carbon concentration and the zooplankton‐derived DOM was considerably transformed at molecular and bulk elemental levels over the incubation period. The C : N ratio (calculated from the obtained molecular formulae) increased while the functional diversity decreased over the incubation time. In addition, molecular indices pointed to a reduced bioavailability of DOM at the end of the experiment. These findings show that zooplankton excreta are a source of labile organic matter that is quickly metabolized by the prokaryotic community. Therefore, a fraction of carbon is shunted from transfer to secondary consumers similarly to the viral shunt, suggesting that the zooplankton–prokaryotic interactions play an important role in the ocean's carbon cycle.

Modeling total predation to avoid perverse outcomes from cat control in a data‐poor island ecosystem - Michaela Plein; Katherine R. O'Brien; Matthew H. Holden; Matthew P. Adams; Christopher M. Baker; Nigel G. Bean; Scott A. Sisson; Michael Bode; Kerrie L. Mengersen; Eve McDonald‐Madden (Conservation Biology, 2022)
Data‐hungry, complex ecosystem models are often used to predict the consequences of threatened species management, including perverse outcomes. Unfortunately, this approach is impractical in the many systems that have insufficient data to parameterize ecosystem interactions or reliably calibrate or validate such models. We devised a different approach composed of a minimum realistic model that guides decisions in data‐ and resource‐scarce systems. We applied our approach to a case study in an invaded ecosystem from Christmas Island, Australia, where there are concerns that cat ( Felis catus ) eradication to protect native species, including the red‐tailed tropicbird ( Phaethon rubricauda ), could release mesopredation by invasive rats ( Rattus rattus ). We used biophysical constraints (metabolic demand) and observable parameters (e.g., prey preferences) to identify the combined cat and rat abundances that could threaten the tropicbird population. The population of tropicbirds was not sustained when predated by 1607 rats (95% credible interval [CI]: 103–5910) in the absence of cats and 21 cats (95% CI: 2–82) in the absence of rats. For every cat removed from the island, the bird's net population growth rate improved, provided rats did not increase by more than 77 individuals (95% CI: 30–174). Thus, in this context, 1 cat is equivalent to 30–174 rats. Our methods are especially useful for on‐the‐ground predator control in the absence of knowledge of predator–predator interactions to determine whether current abundance of predators threatened the prey population of interest; managing only 1 predator species was sufficient to protect the prey species given potential release of another predator; and control of multiple predator species was needed to meet the conservation goal. With our approach limited information can be used for maximum value in data‐poor systems because it shifts the focus from predicting future trajectories to identifying conditions that impede conservation.

Trophic Structure of Neuston Across Tropical and Subtropical Oceanic Provinces Assessed With Stable Isotopes - Rui Albuquerque; Antonio Bode; Juan Ignacio González-Gordillo; Carlos M. Duarte; Henrique Queiroga (Frontiers in Marine Science, 2021)
The marine neuston, organisms living in the vicinity of the ocean surface, is one of the least studied zooplankton groups. Neuston occupies a restricted ecological niche and is affected by a wide range of endogenous and exogenous processes while also being a food source to zooplankton fish migrating from the deep layers and seabirds. In this study, the neustonic communities were characterized along the Malaspina global expedition sampling tropical and subtropical oceanic provinces using stable carbon and nitrogen isotopes to explore their trophic structure and relationships with environmental variables. The differences in stable isotopes mirrored the patterns in environmental characteristics of each province. High δ 13 C values were associated with atmospheric carbon inputs, while the presence of dinoflagellates, coccolithophorids, and upwelling influence is related to low δ 13 C values. Similarly, provinces presenting high δ 15 N values were associated with denitrification and nitrate diffusive fluxes, whereas the presence of low δ 15 N is attributable to nitrogen supplied through N 2 fixation by diazotrophs. Neuston showed a large overlap among the isotopic niches of four functional groups, with chaetognaths and detritivores generally exhibiting a smaller degree of overlap compared to carnivores and omnivores/herbivores. These results support the hypothesis of a common trophic structure in the neuston community across the ocean. However, the size of the niche, small in coastal areas and those influenced by upwelling and large in oligotrophic regions, and their overlap, low in more productive provinces and high in oligotrophic provinces, may be associated with food availability. Small trophic niches are associated with a dominance of specialized over-opportunistic feeding in productive environments.

The role of alanine glyoxylate transaminase-2 (agxt2) in β-alanine and carnosine metabolism of healthy mice and humans - Jan Stautemas; Natalia Jarzebska; Zhou Xiang Shan; Laura Blancquaert; Inge Everaert; Sarah de Jager; Siegrid De Baere; Arne Hautekiet; Anneke Volkaert; Filip B. D. Lefevere; Jens Martens-Lobenhoffer; Stefanie M. Bode-Böger; et al. (European Journal of Applied Physiology, 2020)

Case–Case Comparison of Candida auris Versus Other Candida Species Bloodstream Infections: Results of an Outbreak Investigation in Colombia - Diego H. Caceres; Sandra M. Rivera; Paige A. Armstrong; Patricia Escandon; Nancy A. Chow; Maria Victoria Ovalle; Jorge Díaz; Gordana Derado; Soraya Salcedo; Indira Berrio; Andres Espinosa-Bode; Carmen Varón; et al. (Mycopathologia, 2020)

Climate and Local Hydrography Underlie Recent Regime Shifts in Plankton Communities off Galicia (NW Spain) - Antonio Bode; Marta Álvarez; Luz María García García; Maria Ángeles Louro; Mar Nieto-Cid; Manuel Ruíz-Villarreal; Marta M. Varela (Oceans, 2020)
A 29-year-long time series (1990–2018) of phyto- and zooplankton abundance and composition is analyzed to uncover regime shifts related to climate and local oceanography variability. At least two major shifts were identified: one between 1997 and 1998, affecting zooplankton group abundance, phytoplankton species assemblages and climatic series, and a second one between 2001 and 2002, affecting microzooplankton group abundance, mesozooplankton species assemblages and local hydrographic series. Upwelling variability was relatively less important than other climatic or local oceanographic variables for the definition of the regimes. Climate-related regimes were influenced by the dominance of cold and dry (1990–1997) vs. warm and wet (1998–2018) periods, and characterized by shifts from low to high life trait diversity in phytoplankton assemblages, and from low to high meroplankton dominance for mesozooplankton. Regimes related to local oceanography were defined by the shift from relatively low (1990–2001) to high (2002–2018) concentrations of nutrients provided by remineralization (or continental inputs) and biological production, and shifts from a low to high abundance of microzooplankton, and from a low to high trait diversity of mesozooplankton species assemblages. These results align with similar shifts described around the same time for most regions of the NE Atlantic. This study points out the different effects of large-scale vs. local environmental variations in shaping plankton assemblages at multiannual time scales.

Simultaneous invasive alien predator eradication delivers the best outcomes for protected island species - Christopher M. Baker; Michaela Plein; Rabith Shaikh; Michael Bode (Biological Invasions, 2020)

Quantitative trait loci and differential gene expression analyses reveal the genetic basis for negatively associated β-carotene and starch content in hexaploid sweetpotato [Ipomoea batatas (L.) Lam.] - Dorcus C. Gemenet; Guilherme da Silva Pereira; Bert De Boeck; Joshua C. Wood; Marcelo Mollinari; Bode A. Olukolu; Federico Diaz; Veronica Mosquera; Reuben T. Ssali; Maria David; Mercy N. Kitavi; Gabriela Burgos; et al. (Theoretical and Applied Genetics, 2020)
Key message β-Carotene content in sweetpotato is associated with the Orange and phytoene synthase genes; due to physical linkage of phytoene synthase with sucrose synthase , β-carotene and starch content are negatively correlated. Abstract In populations depending on sweetpotato for food security, starch is an important source of calories, while β-carotene is an important source of provitamin A. The negative association between the two traits contributes to the low nutritional quality of sweetpotato consumed, especially in sub-Saharan Africa. Using a biparental mapping population of 315 F 1 progeny generated from a cross between an orange-fleshed and a non-orange-fleshed sweetpotato variety, we identified two major quantitative trait loci (QTL) on linkage group (LG) three (LG3) and twelve (LG12) affecting starch, β-carotene, and their correlated traits, dry matter and flesh color. Analysis of parental haplotypes indicated that these two regions acted pleiotropically to reduce starch content and increase β-carotene in genotypes carrying the orange-fleshed parental haplotype at the LG3 locus. Phytoene synthase and sucrose synthase, the rate-limiting and linked genes located within the QTL on LG3 involved in the carotenoid and starch biosynthesis, respectively, were differentially expressed in Beauregard versus Tanzania storage roots. The Orange gene, the molecular switch for chromoplast biogenesis, located within the QTL on LG12 while not differentially expressed was expressed in developing roots of the parental genotypes. We conclude that these two QTL regions act together in a cis and trans manner to inhibit starch biosynthesis in amyloplasts and enhance chromoplast biogenesis, carotenoid biosynthesis, and accumulation in orange-fleshed sweetpotato. Understanding the genetic basis of this negative association between starch and β-carotene will inform future sweetpotato breeding strategies targeting sweetpotato for food and nutritional security.

Zooplankton and Micronekton Active Flux Across the Tropical and Subtropical Atlantic Ocean - Santiago Hernández-León; María Pilar Olivar; María Luz Fernández de Puelles; Antonio Bode; Arturo Castellón; Cristina López-Pérez; Víctor M. Tuset; José Ignacio González-Gordillo (Frontiers in Marine Science, 2019)

MDPI Oceans: A New Publication Channel for Open Access Science Focused on the Ocean - Antonio Bode; Fátima Abrantes; Agostinho Antunes; Alvise Benetazzo; Chen-Tung Arthur Chen; Emmanuel Devred; Martin Gade; Eulàlia Gràcia; Jochen Horstmann; Diego Macías; Joseph M. Maina; Pere Masqué; et al. (Oceans, 2019)
The ocean is the most important subsystem of the Earth’s climate system and functions as its heart, regulating the energy distribution of the planet [...]

Changes in phytoplankton production and upwelling intensity off A Coruña (NW Spain) for the last 28 years - Antonio Bode; Marta Álvarez; Manuel Ruíz-Villarreal; Marta M. Varela (Ocean Dynamics, 2019)

The Decision Decoding ToolBOX (DDTBOX) – A Multivariate Pattern Analysis Toolbox for Event-Related Potentials - Stefan Bode; Daniel Feuerriegel; Daniel Bennett; Phillip M. Alday (Neuroinformatics, 2019)

Biological N2 Fixation in the Upwelling Region off NW Iberia: Magnitude, Relevance, and Players - Víctor Moreira-Coello; Beatriz Mouriño-Carballido; Emilio Marañón; Ana Fernández-Carrera; Antonio Bode; Marta M. Varela (Frontiers in Marine Science, 2017)

Molecular mechanisms of green tea polyphenols with protective effects against skin photoaging - Eunmiri Roh; Jong-Eun Kim; Jung Yeon Kwon; Jun Seong Park; Ann M. Bode; Zigang Dong; Ki Won Lee (Critical Reviews in Food Science and Nutrition, 2017)

Ensemble ecosystem modeling for predicting ecosystem response to predator reintroduction - Christopher M. Baker; Ascelin Gordon; Michael Bode (Conservation Biology, 2017)
Introducing a new or extirpated species to an ecosystem is risky, and managers need quantitative methods that can predict the consequences for the recipient ecosystem. Proponents of keystone predator reintroductions commonly argue that the presence of the predator will restore ecosystem function, but this has not always been the case, and mathematical modeling has an important role to play in predicting how reintroductions will likely play out. We devised an ensemble modeling method that integrates species interaction networks and dynamic community simulations and used it to describe the range of plausible consequences of 2 keystone‐predator reintroductions: wolves (Canis lupus) to Yellowstone National Park and dingoes (Canis dingo) to a national park in Australia. Although previous methods for predicting ecosystem responses to such interventions focused on predicting changes around a given equilibrium, we used Lotka–Volterra equations to predict changing abundances through time. We applied our method to interaction networks for wolves in Yellowstone National Park and for dingoes in Australia. Our model replicated the observed dynamics in Yellowstone National Park and produced a larger range of potential outcomes for the dingo network. However, we also found that changes in small vertebrates or invertebrates gave a good indication about the potential future state of the system. Our method allowed us to predict when the systems were far from equilibrium. Our results showed that the method can also be used to predict which species may increase or decrease following a reintroduction and can identify species that are important to monitor (i.e., species whose changes in abundance give extra insight into broad changes in the system). Ensemble ecosystem modeling can also be applied to assess the ecosystem‐wide implications of other types of interventions including assisted migration, biocontrol, and invasive species eradication.

A systematic review and meta-analysis on Staphylococcus aureus carriage in psoriasis, acne and rosacea - J. E. E. Totté; W. T. van der Feltz; L. G. M. Bode; A. van Belkum; E. J. van Zuuren; S. G. M. A. Pasmans (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Chemopreventive Effects of Licorice and Its Components - Ann M. Bode; Zigang Dong (Current Pharmacology Reports, 2015)

Erratum to: Glycolytic genes in cancer cells are more than glucose metabolic regulators - Zhe-Yu Hu; Lanbo Xiao; Ann M. Bode; Zigang Dong; Ya Cao (Journal of Molecular Medicine, 2014)

Glycolytic genes in cancer cells are more than glucose metabolic regulators - Zhe-Yu Hu; Lanbo Xiao; Ann M. Bode; Zigang Dong; Ya Cao (Journal of Molecular Medicine, 2014)

Minimizing the Cost of Keeping Options Open for Conservation in a Changing Climate - MORENA MILLS; SAM NICOL; JESSIE A. WELLS; JOSÉ J. LAHOZ‐MONFORT; BRENDAN WINTLE; MICHAEL BODE; MARTIN WARDROP; TERRY WALSHE; WILLIAM J. M. PROBERT; MICHAEL C. RUNGE; HUGH P. POSSINGHAM; EVE MCDONALD MADDEN (Conservation Biology, 2014)
Policy documents advocate that managers should keep their options open while planning to protect coastal ecosystems from climate‐change impacts. However, the actual costs and benefits of maintaining flexibility remain largely unexplored, and alternative approaches for decision making under uncertainty may lead to better joint outcomes for conservation and other societal goals. For example, keeping options open for coastal ecosystems incurs opportunity costs for developers. We devised a decision framework that integrates these costs and benefits with probabilistic forecasts for the extent of sea‐level rise to find a balance between coastal ecosystem protection and moderate coastal development. Here, we suggest that instead of keeping their options open managers should incorporate uncertain sea‐level rise predictions into a decision‐making framework that evaluates the benefits and costs of conservation and development. In our example, based on plausible scenarios for sea‐level rise and assuming a risk‐neutral decision maker, we found that substantial development could be accommodated with negligible loss of environmental assets. Characterization of the Pareto efficiency of conservation and development outcomes provides valuable insight into the intensity of trade‐offs between development and conservation. However, additional work is required to improve understanding of the consequences of alternative spatial plans and the value judgments and risk preferences of decision makers and stakeholders. Minimizando el Costo de Mantener Opciones Abiertas para la Conservación en un Clima Cambiante

Assisting vascular access surgery planning for hemodialysis by using MR, image segmentation techniques, and computer simulations - M. A. G. Merkx; A. S. Bode; W. Huberts; J. Oliván Bescós; J. H. M. Tordoir; M. Breeuwer; F. N. van de Vosse; E. M. H. Bosboom (Medical & Biological Engineering & Computing, 2013)

Recent advances in 2D and 3D in vitro systems using primary hepatocytes, alternative hepatocyte sources and non-parenchymal liver cells and their use in investigating mechanisms of hepatotoxicity, cell signaling and ADME - Patricio Godoy; Nicola J. Hewitt; Ute Albrecht; Melvin E. Andersen; Nariman Ansari; Sudin Bhattacharya; Johannes Georg Bode; Jennifer Bolleyn; Christoph Borner; Jan Böttger; Albert Braeuning; Robert A. Budinsky; et al. (Archives of Toxicology, 2013)

Pathologic progression of mammary carcinomas in a C3(1)/SV40 T/t-antigen transgenic rat model of human triple-negative and Her2-positive breast cancer - M. J. Hoenerhoff; M. A. Shibata; A. Bode; J. E. Green (Transgenic Research, 2011)

Degree of oligotrophy controls the response of microbial plankton to Saharan dust - Emilio Marañén; Ana Fernández; Beatriz Mouriño-Carballido; Sandra MartÍnez-GarcÍa; Eva Teira; Pedro Cermeño; Paloma Chouciño; MarÍa Huete-Ortega; Emilio Fernández; Alejandra Calvo-DÍaz; Xosé Anxelu G. Morán; Antonio Bode; et al. (Limnology and Oceanography, 2010)
To determine the effects of Saharan dust on the abundance, biomass, community structure, and metabolic activity of oceanic microbial plankton, we conducted eight bioassay experiments between ca. 30°N and 30°S in the central Atlantic Ocean. We found that, although bulk abundance and biomass tended to remain unchanged, different groups of phytoplankton and bacterioplankton responded differently to Saharan dust addition. The predominant type of metabolic response depended on the ecosystem's degree of oligotrophy and was modulated by competition for nutrients between phytoplankton and heterotrophic bacteria. The relative increase in bacterial production, which was the dominant response to dust addition in ultraoligotrophic environments, became larger with increasing oligotrophy. In contrast, primary production, which was stimulated only in the least oligotrophic waters, became less responsive to dust as the ecosystem's degree of oligotrophy increased. Given the divergent consequences of a predominantly bacterial vs. phytoplanktonic response, dust inputs can, depending on the ecosystem's degree of oligotrophy, stimulate or weaken biological CO 2 drawdown. Thus, the biogeochemical implications of changing dust fluxes might not be universal, but variable through both space and time.

Safeguarding Biodiversity and Ecosystem Services in the Little Karoo, South Africa - BENIS N. EGOH; BELINDA REYERS; JOSIE CARWARDINE; MICHAEL BODE; PATRICK J. O'FARRELL; KERRIE A. WILSON; HUGH P. POSSINGHAM; MATHIEU ROUGET; WILLEM De LANGE; DAVID M. RICHARDSON; RICHARD M. COWLING (Conservation Biology, 2010)
Global declines in biodiversity and the widespread degradation of ecosystem services have led to urgent calls to safeguard both. Responses to this urgency include calls to integrate the needs of ecosystem services and biodiversity into the design of conservation interventions. The benefits of such integration are purported to include improvements in the justification and resources available for these interventions. Nevertheless, additional costs and potential trade‐offs remain poorly understood in the design of interventions that seek to conserve biodiversity and ecosystem services. We sought to investigate the synergies and trade‐offs in safeguarding ecosystem services and biodiversity in South Africa's Little Karoo. We used data on three ecosystem services—carbon storage, water recharge, and fodder provision—and data on biodiversity to examine several conservation planning scenarios. First, we investigated the amount of each ecosystem service captured incidentally by a conservation plan to meet targets for biodiversity only while minimizing opportunity costs. We then examined the costs of adding targets for ecosystem services into this conservation plan. Finally, we explored trade‐offs between biodiversity and ecosystem service targets at a fixed cost. At least 30% of each ecosystem service was captured incidentally when all of biodiversity targets were met. By including data on ecosystem services, we increased the amount of services captured by at least 20% for all three services without additional costs. When biodiversity targets were reduced by 8%, an extra 40% of fodder provision and water recharge were obtained and 58% of carbon could be captured for the same cost. The opportunity cost (in terms of forgone production) of safeguarding 100% of the biodiversity targets was about US$500 million. Our results showed that with a small decrease in biodiversity target achievement, substantial gains for the conservation of ecosystem services can be achieved within our biodiversity priority areas for no extra cost.

Heterogeneity of the humoral immune response following Staphylococcus aureus bacteremia - N. J. Verkaik; H. A. Boelens; C. P. de Vogel; M. Tavakol; L. G. M. Bode; H. A. Verbrugh; A. van Belkum; W. J. B. van Wamel (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Phenotype–environment mismatches reduce connectivity in the sea - D. J. Marshall; K. Monro; M. Bode; M. J. Keough; S. Swearer (Ecology Letters, 2010)
The connectivity of marine populations is often surprisingly lower than predicted by the dispersal capabilities of propagules alone. Estimates of connectivity, moreover, do not always scale with distance and are sometimes counterintuitive. Population connectivity requires more than just the simple exchange of settlers among populations: it also requires the successful establishment and reproduction of exogenous colonizers. Marine organisms often disperse over large spatial scales, encountering very different environments and suffering extremely high levels of post‐colonization mortality. Given the growing evidence that such selection pressures often vary over spatial scales that are much smaller than those of dispersal, we argue that selection will bias survival against exogenous colonizers. We call this selection against exogenous colonizers a phenotype–environment mismatch and argue that phenotype–environment mismatches represent an important barrier to connectivity in the sea. Crucially, these mismatches may operate independently of distance and thereby have the potential to explain the counterintuitive patterns of connectivity often seen in marine environments. We discuss how such mismatches might alter our understanding and management of marine populations. Ecology Letters (2010) 13: 128–140

Identification, genome mapping, and CTCF binding of potential insulators within the FXYD5-COX7A1 locus of human Chromosome 19q13.12 - Sergey B. Akopov; Vera M. Ruda; Vera V. Batrak; Anna S. Vetchinova; Igor P. Chernov; Lev G. Nikolaev; Jürgen Bode; Eugene D. Sverdlov (Mammalian Genome, 2006)

Immunogold-labeled S-phase neoblasts, total neoblast number, their distribution, and evidence for arrested neoblasts in Macrostomum lignano (Platyhelminthes, Rhabditophora) - A. Bode; W. Salvenmoser; K. Nimeth; M. Mahlknecht; Z. Adamski; R. M. Rieger; R. Peter; P. Ladurner (Cell and Tissue Research, 2006)

Effect of L-arginine supplementation on NO production in man - Stefanie M. Bode-Böger (European Journal of Clinical Pharmacology, 2006)

Measurement of asymmetric dimethylarginine (ADMA) in human plasma: from liquid chromatography estimation to liquid chromatography-mass spectrometry quantification - Jens Martens-Lobenhoffer; Stefanie M. Bode-Böger (European Journal of Clinical Pharmacology, 2006)

Evaluation of Cancer-Preventive Activity and Structure–Activity Relationships of 3-Demethylubiquinone Q2, Isolated from the Ascidian Aplidium glabrum, and its Synthetic Analogs - Sergey N. Fedorov; Oleg S. Radchenko; Larisa K. Shubina; Nadezhda N. Balaneva; Ann M. Bode; Valentin A. Stonik; Zigang Dong (Pharmaceutical Research, 2006)

Field evaluation for resistance to the black rot pathogen Xanthomonas campestris pv. campestris in cabbage (Brassica oleracea) - Brita Dahl Jensen; Said M. S. Massomo; Ignas S. Swai; John Hockenhull; Sven Bode Andersen (European Journal of Plant Pathology, 2005)

Marine Alkaloid Polycarpine and Its Synthetic Derivative Dimethylpolycarpine Induce Apoptosis in JB6 Cells Through p53- and Caspase 3-Dependent Pathways - Sergey N. Fedorov; Ann M. Bode; Valentin A. Stonik; Irina A. Gorshkova; Patricia C. Schmid; Oleg S. Radchenko; Evgueni V. Berdyshev; Zigang Dong (Pharmaceutical Research, 2004)

Increased glycolysis as protective adaptation of energy depleted, degenerating human hibernating myocardium - Achim M. Vogt; Albrecht Elsässer; Holger Nef; Christoph Bode; Wolfgang Kübler; Jutta Schaper (Molecular and Cellular Biochemistry, 2003)

Effects of ENU dosage on mouse strains - Monica J. Justice; Don A. Carpenter; Jack Favor; Angelika Neuhauser-Klaus; Martin Hrabé de Angelis; Dian Soewarto; Amy Moser; Sabine Cordes; Darla Miller; Verne Chapman; John S. Weber; Eugene M. Rinchik; et al. (Mammalian Genome, 2000)

Effects of very low dose and enteric-coated acetylsalicylic acid on prostacyclin and thromboxane formation and on bleeding time in healthy subjects - S. M. Bode-Böger; R. H. Böger; M. Schubert; J. C. Frölich (European Journal of Clinical Pharmacology, 1998)

Long-wavelength global gravity field models: GRIM4-S4, GRIM4-C4 - P. Schwintzer; C. Reigber; A. Bode; Z. Kang; S. Y. Zhu; F.-H. Massmann; J. C. Raimondo; R. Biancale; G. Balmino; J. M. Lemoine; B. Moynot; J. C. Marty; et al. (Journal of Geodesy, 1997)